ANALISIS PERTIMBANGAN HAKIM DALAM MENOLAK PERKARA CERAI GUGAT KARENA MASIH MELAKUKAN HUBUNGAN SEKSUAL SUAMI ISTRI: (Studi Putusan Nomor 111/Pdt.G/2019/PA.Ptk) - Nurhidayah, Ririn; Wagiyem, Wagiyem; Ardiansyah, Ardiansyah (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This essay is written to answer the questions set forth in the problem formulation, namely: first, what is the legal basis for the judge in deciding the case decision number 111/Pdt.G/2019/PA.Ptk? second, what is the judge's consideration in refusing to file a lawsuit because there is still a husband and wife relationship in decision number 111/Pdt.G/2019/PA.Ptk? This research is a qualitative research with a descriptive approach. The data sources of this research consist of primary sources in the form of document manuscripts and secondary sources, namely KHI, Law Number 1 of 1974, Government Regulation Number 9 of 1975, books and journals that discuss the decisions of the cases studied. Furthermore, the data that was collected was analyzed with a deductive mindset to analyze the judge's decision to reject the divorce case because the plaintiff and the defendant were still having sexual relations. Based on the analysis carried out, the researchers concluded that the chronology of the divorce lawsuit against married couples who were still having sex was rejected by the Panel of Judges at the Pontianak Religious Court, in decision number 111/Pdt.G/2019/PA.Ptk it was the wife who initially proposed lawsuit because her husband who became a drug addict, was then imprisoned for six years and three months and there were constant disputes. However, in the process of the lawsuit, the plaintiff and the defendant still had a husband and wife sexual relationship. Based on this, the Majlis Hakim stated that the arguments of the plaintiff's claim for divorce were legally flawed. In the sadd az-zari'ah analysis, the judge's decision is appropriate because it aims to avoid avoiding a maslahah act that results in harm that the initial law of marriage is permissible but because there is still sexual intercourse which is feared to cause pregnancy, divorce is not allowed.